CALCIUM SALT OF CARBOXYMETHYLED AEGLE MARMELOS (BAEL FRUIT) GUM: A NOVEL SUPERDISINTEGRANT FOR FAST DISINTEGRATING TABLETS. - Dhruv, Dev; Diksha, Rai; N, Prasad D (Asian Journal of Pharmaceutical Research and Development, 2018)
The present study was carried out for the preparation of modified Aegle marmelos gum as natural superdisintegrant and assessed it on various parameters for preparing fast dissolving dosage form. The extracted gum from Aegle marmelos fruit is chemically modified by carrying out its carboxymethylation and further complexed with Calcium chloride. Therefore, the natural Superdisintegrant prepared from Aegle marmelos gum followed swelling and wetting mechanism for disintegration of the dosage form. The change in the functional groups of the extracted gum, carboxymethyled gum and the calcium complexed gum was studied by FT-IR spectrophotometer and DSC studies. Pre-compression parameters of the tablet such as Swelling index, bulk density, tapped density, carr’s index, angle of repose and hausner’s ratio were determined. Dummy tablets containing calcium complexed Aegle marmelos gum were formulated to check the disintegrating efficiency of the tablets. The disintegrating properties of calcium complexed Aegle marmelos gum as superdisintegrant was compared with the marketed Superdisintegrant Sodium starch glycolate. The comparison between both the formulations containing different superdisintegrants in various batches was done to check the disintegrating efficiency of the modified Aegle marmelos gum as superdisintegrant. The disintegrating time for calcium complexed Aegle marmelos gum was observed to be 1min±2sec to 1min±5sec showing good disintegrating properties.The present study may serve as a prototype approach for formulation and development of novel superdisintegrant from various natural gums.